Ketika Misri Masih Dimainkan, Ketika Tari Masih Dipentaskan - Ikhwan, Mahfud (MAARIF, 2023)
Muhammadiyah is stereotyped as an anti-art movement and dry of culture. In fact, in practice, efforts to use art and culture as an expression of Muhammadiyah are not non-existent and have not been carried out at all, both at the grassroots and at the elite level. The nature of the movement which naturally clashes with culture and the tendency to smooth over diversity in the name of organizational order means that these efforts are not continued or allowed to die.